Estudio de prefactibilidad para la instalación de una planta empaquetadora y exportadora de aguaymanto (Physalis peruviana) fresco y en pulpa congelada a Canadá - Avila Luna, Juan Manuel (2019)
The present pre-feasibility study evaluated the viability of implement a production plant of fresh and frozen pulp of Physalis Peruviana (goldenberry or “aguaymanto”) The Canadian market was analyzed through virtual surveys in its two main cities (Toronto and Montreal) and the specific demand for the project was 891.514 kg for the fresh fruit line and 201.962 kg for frozen fruits by 2022. About the raw materials, it was determined that the main producing areas of aguaymanto in the Peruvian country are Cajamarca and Ayacucho. The farmers sell the berries at approximately S/ 2.000 per ton. In what refers to the plant location, it was determined that the ideal city is Paita (one of the cities of the department of Piura) considering key factors like proximity to raw materials, operating cost of seaports, closeness to the seaport, among others. About the project engineering, the production process of fresh and frozen pulp of Physalis Peruviana was investigated, looking for machinery and equipment according to the production capacity required, which represent an investment of S/ 217.660. Finally, the economic and financial viability of the project was determined through ratios like S/ 6.018.810 and S/7.895.305 of VAN, 43% and 76% of TIR, and a recovery period of 3,11 and 1,98 years, respectively.